Electrical Transport in Iron Phosphate-Based Glass-(Ceramics): Insights into the Role of B2O3 and HfO2 from Model-Free Scaling Procedures - Bafti, Arijeta; Kubuki, Shiro; Ertap, Huseyin; Yuksek, Mustafa; Karabulut, Mevlut; Mogus-Milankovic, Andrea; Pavic, Luka (Mdpi, 2022)
In this work, we report the effect of the addition of modifiers and network formers on the polaronic transport in iron phosphate glasses (IPG) in two systems of HfO2-B2O3-Fe2O3-P2O5, to which up to 8 mol% boron and hafnium are added. The addition of oxides significantly changes the Fe2+/Fe-total ratio, thus directly affecting the polaron number density and consequently controlling DC conductivity trends for both series studied by impedance spectroscopy. Moreover, we found that short-range polaron dynamics are also under the influence of structural changes. Therefore, we have studied them in detail using model-free scaling procedures, Summerfield and Sidebottom scaling. An attempt to construct a super-master curve revealed that in addition to change in polaron number density, also the polaron hopping lengths change, and Sidebottom scaling yields a super-master curve. The spatial extent of the localized motion of polarons is correlated with polaron number density and two distinct regions are observed. A strong increase in the spatial extent of the polaron hopping jump could be related either to the structural changes due to the addition of HfO2 and B2O3 and their effects on the formation of polarons or to an inherent property of polaron transport in IP glasses with low polaron number density.
Keywords: iron phosphate glass; small polaron hopping; impedance spectroscopy; scaling procedures; model-free; conductivity and permittivity spectra